Proceedings of the 2014 ACM International Symposium on Wearable Computers: Adjunct Program 2014
DOI: 10.1145/2641248.2645638
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged work with head mounted displays

Abstract: This paper sums up the main results from a research project focusing on prolonged work with head mounted displays and the effect on physiological and mental strain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 1 publication
4
3
0
Order By: Relevance
“…As a consequence of the stretch being too tight, half of the participants felt physical discomfort and 75% of them felt a bit of fatigue but still tolerable after using the headset. However, these outcomes concur with the results of a previous research (Wille et al 2014) on smart eyewear (commercialized HMD) . Indeed, their results showed that even that there were no significant quantitative results proving a visual fatigue of the users (such as blink rate, etc.)…”
Section: Ergonomicssupporting
confidence: 91%
“…As a consequence of the stretch being too tight, half of the participants felt physical discomfort and 75% of them felt a bit of fatigue but still tolerable after using the headset. However, these outcomes concur with the results of a previous research (Wille et al 2014) on smart eyewear (commercialized HMD) . Indeed, their results showed that even that there were no significant quantitative results proving a visual fatigue of the users (such as blink rate, etc.)…”
Section: Ergonomicssupporting
confidence: 91%
“…As a consequence of the stretch being too tight, half of the participants felt physical discomfort and 75% of them felt a bit of fatigue but still tolerable after using the headset. However, these outcomes concur with the results of a previous research on smart eyewear (commercialized HMD) [19]. Indeed, their results showed that even that there were no significant quantitative results proving a visual fatigue of the users (such as blink rate, etc.)…”
Section: Ergonomicssupporting
confidence: 90%
“…It has been shown for example that the unfamiliarity with AR could result in lower performance as has been reported in prior work [74]. In addition, the user experience in both conditions has been rated very positively with a higher score for AR regarding the hedonic factors represented by Stimulation and Novelty.…”
Section: Usability and User Experiencesupporting
confidence: 61%